An empirical evaluation of the performance of financial protection indicators for UHC monitoring: Evidence from Burkina Faso - Benjamin Sas Trakinsky; Bridget R. Irwin; Hervé J.-L. Guéné; Karen A. Grépin (Elsevier, 2020)
Achieving Universal Health Coverage (UHC) has been recognized as one of the Sustainable Development Goals (SDGs) and includes both ensuring access to health services and providing financial protection (FP) against using these services. Currently, progress towards achieving the FP component of UHC is assessed using the catastrophic health expenditure budget share indicator, which estimates the proportion of the population with health expenditures exceeding 10% of total income or consumption. Other indicators exist, however, and are widely used in the literature, yet few studies have compared the usefulness of these indicators for UHC monitoring. Using panel data from Burkina Faso, this paper seeks to evaluate the performance of common FP indicators based on three properties: (1) their ability to identify those most at risk of financial hardship (i.e. the poor), (2) their ability to detect households with health shocks, and (3) their sensitivity to seasonal variation. Our results indicate that, while some indicators perform better in certain conditions than others, none are without limitation. Indeed, despite being the best able to differentiate households who have experienced a health shock, the official SDG indicator performs the worst at identifying the poorest group of the population and is the most sensitive to seasonal variation. As such, more research is needed in order to improve the measurement of FP such that progress towards achieving UHC can be accurately monitored.